Potensi Pengunaan Eco Enzyme Sebagai Biokatalis Dalam Penguraian Minyak dan Lemak pada Air Limbah Domestik - Temmy Wikaningrum; Efli Pratamadina (Fakultas Teknik, 2022)
The surface water quality is getting more attention at this time, given the lower quality in some areas of West Java. Mostly the causes of the decline in water quality is due to the disposal of domestic wastewater. Oil and grease is one of the parameter in domestic wastewater that must be considered. Eco enzyme is made from the anaerobic fermentation of organic waste from fruits and vegetables which has a a versatile performance. The aims of this study is to determine whether eco enzyme made from citrus waste has the potential to be used to degrade the concentration of oil and fat in domestic wastewater. The sample used was artificially made from domestic wastewater samples which were intentionally added to oil and grease so that the initial concentration was 19.82 mg/L. In the sample that had been added 5% eco enzyme, the concentration of oil and grease managed to decrease to 13.84 mg/L after 9 days of observation, compared to that which did not add eco enzyme to 15.93 mg/L. The t Test statistical analysis showed that the oil and grease concentration reduction in the two treatments was significant, but the ANOVA analysis results showed that the two treatments did not differ significantly.